2008
DOI: 10.3390/ijms9091772
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heat Treatment on the Physical Properties and Surface Roughness of Turkish Hazel (Corylus colurna L.) Wood

Abstract: Heat treatment is often used to improve the dimensional stability of wood. In this study, the effects of heat treatment on the physical properties and surface roughness of Turkish Hazel (Corylus colurna L.) wood were examined. Samples obtained from Kastamonu Forest Enterprises, Turkey, were subjected to heat treatment at varying temperatures and for different durations. The physical properties of heat-treated and control samples were tested, and oven-dry density, air-dry density, and swelling properties were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 16 publications
9
40
1
7
Order By: Relevance
“…Boonstra et al (2007b) reported a 10% and 8.5% decrease in density for heat-treated Scots pine and Norway spruce, respectively. The results are parallel to previously published reports for different species (Yildiz et al 2006;Korkut et al 2008;Gunduz et al 2009). …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Boonstra et al (2007b) reported a 10% and 8.5% decrease in density for heat-treated Scots pine and Norway spruce, respectively. The results are parallel to previously published reports for different species (Yildiz et al 2006;Korkut et al 2008;Gunduz et al 2009). …”
Section: Resultssupporting
confidence: 82%
“…Degradation of the cellulose polymer, decreasing the DP, was suggested as the main cause for losses in tensile strength (Kass et al 1970;Esteves and Pereira 2009). Korkut et al (2008) reported that the lowest tensile strengths perpendicular to the grain were at 180 °C for 10 h (2.131 N/mm 2 ) in Red-bud maple (Acer trautvetteri Medw.) wood.…”
Section: Tensile Strength Parallel To the Grain (Ts)mentioning
confidence: 99%
“…Wood species that have no commercial value can be heat-treated and, in this way, a new use can be found for these species. On the other hand, the major disadvantage of this method is the reduction of mechanical resistance (Kubojima et al, 2000;Reiterer and Sinn, 2002;Epmeier et al, 2004;Unsal and Ayrilmis, 2005;Korkut et al, 2008). Temperatures over 150 °C permanently modify the physical and mechanical properties of wood (Mitchell, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Grau de redução similar ao observado no presente estudo para a dureza no plano tangencial e radial também foi encontrado por Korkut et al (2008), para a madeira de Pinus sylvestris L., submetida ao tratamento a 150°C. Os autores encontraram reduções em 14,68% e 18,31% no plano tangencial para o tratamento de 2 e 6 h, respectivamente e 10,65% e 13,80% no plano radial.…”
Section: Resultsunclassified